Purification and Mass Spectrometric Analysis of the κ Opioid Receptor - Wannemacher, Kenneth M. (2008)
A clonal human embryonic kidney (HEK) 293 cell line was established that stably expressed the rat κ-opioid receptor (rKOR) with a FLAG epitope at the amino terminus. The K(d) for [(3)H]diprenorphine was 1.1 ± 0.2 nM, and the B(max) was 2.6 ± 0.4 pmoles/mg. Dynorphin A (1–13), U69,593 and naloxone competitively inhibited [(3)H]diprenorphine binding with K(i) values of 2.0, 18 and 18 nM, respectively, in good agreement with previously reported affinities for the unmodified receptor. U69,593 stimulated [(35)S]GTPγS binding in a concentration-dependent manner and caused phosphorylation of mitogen-activated protein (MAP) kinase, indicating that the activated epitope-tagged receptor triggered appropriate signaling pathways. Immunoblot analysis demonstrated that two immunoreactive receptor species with apparent molecular masses of 42 and 52 kDa were expressed. Previous studies indicated that the 42 kDa protein was localized intracellularly and was a precursor of the 52 kDa receptor, which was present at the cell surface. rKOR was extracted from transfected HEK 293 cell membranes with n-dodecyl-β-D-maltopyranoside. Sequential use of wheat germ agglutinin chromatography, Sephacryl S300 gel filtration chromatography, anti-FLAG immunoaffinity chromatography and SDS/PAGE permitted purification of the 52 kDa receptor. MALDI-TOF mass spectrometry was used to identify peptides derived from rKOR following sequential in-gel digestion with trypsin and cyanogen bromide. Eighteen rKOR peptides were detected, corresponding to 27.1% coverage of the receptor. Precursor-selective MS/MS confirmed the identity of most of these peptides. In addition, we have identified heat shock protein 70 (HSP70) as a rKOR-interacting protein.